THE EFFECT OF COMPENSATION ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS AN INTERVENING VARIABLE CV. MILLENIA TOTAL SOLUTION PALEMBANG - Sugeng Mianto Fane; Faridatul Munawaruh (Jurnal Manajemen, 2023)
The purpose of this study was to determine the effect of compensation on employee performance with motivation as an intervening variable at CV Millenia Total Solution Palembang. The results showed that the first simple regression analysis that compensation has a positive and significant effect on motivation, compensation has a positive and significant effect on performance. Based on the results of both simple regression analysis can be done with intervening so that it is known that the value of t count 5.396 t table 2.040 can be concluded that motivation is able to become an intervening variable with the calculation of standardized co effientsn for the indirect effect of compensation on performance.